2009
DOI: 10.1007/s00464-009-0718-6
|View full text |Cite
|
Sign up to set email alerts
|

Hiatal hernia repair with mesh: a survey of SAGES members

Abstract: The use of mesh during hiatal hernia repair resulted in a reported recurrence rate which appeared to be lower than that obtained historically without mesh. No one mesh type was clearly superior in terms of avoiding failure and complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
75
0
21

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(96 citation statements)
references
References 49 publications
(60 reference statements)
0
75
0
21
Order By: Relevance
“…The 0% recurrence rate after mesh repair in this study was not replicated in the other trials, perhaps reflecting the encirclement of the esophagus by the mesh prosthesis. However, many surgeons remain reluctant to place mesh fully around the esophagus because of the perceived risks of mesh erosion and hiatal fibrosis at longer term follow-up 5 . Unfortunately, because late follow-up from this study has not been reported, Frantzides et al's results have not addressed this issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 0% recurrence rate after mesh repair in this study was not replicated in the other trials, perhaps reflecting the encirclement of the esophagus by the mesh prosthesis. However, many surgeons remain reluctant to place mesh fully around the esophagus because of the perceived risks of mesh erosion and hiatal fibrosis at longer term follow-up 5 . Unfortunately, because late follow-up from this study has not been reported, Frantzides et al's results have not addressed this issue.…”
Section: Discussionmentioning
confidence: 99%
“…tension-free repair with prosthetic reinforcement, and it is technically straightforward to perform laparoscopically. Whilst good results have been reported from case series of mesh repair, some surgeons are concerned that the potential advantages of mesh repair might be offset by the risk of the mesh eroding into the esophageal lumen, and other complications 5 . Difficulties also occur when assessing the outcomes of mesh repair, as there is great variability between mesh types and configurations, and little standardization of surgical techniques.…”
Section: Introductionmentioning
confidence: 99%
“…In his survey, 24% placed mesh for defects [5 cm, 13% for defects [8 cm, and 9% for [3 cm. Tension on the crura (10%), recurrent hernia (5%), poor crural tissue (5%), and obesity (0.8%) were other indications for mesh placement in this survey [17].…”
Section: Discussionmentioning
confidence: 97%
“…Several repair techniques have been described, the most common one involving the reinforcement of the hiatal closure by implantation of mesh around the esophageal hiatus. Although studies have demonstrated a decrease in the PEH recurrence rate with mesh reinforcement [17,18], this technique remains controversial [15,19,20]. The use of synthetic mesh can lead to dysphagia or odyngophagia in up to 21.7% of patients, likely due to esophageal stenosis and periesophageal mesh-induced fibrosis [5,12,21,22].…”
Section: Discussionmentioning
confidence: 99%